2022
DOI: 10.1155/2022/3851551
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis and Validation of Autophagy-Related Genes and Immune Infiltration in Acute Myocardial Infarction

Abstract: Background. Acute myocardial infarction (AMI) is one of the most critical conditions of coronary heart disease with many uncertainties regarding reduction of ischemia/reperfusion injury, medical treatment strategies, and other aspects. The inflammatory immune response has a bidirectional regulatory role in AMI and plays an essential role in myocardial remodeling after AMI. The purpose of our research was tantamount to explore possible mechanisms of AMI and to analyze the relationship with the immune microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Ispinesib, a novel, potent, selective, and allosteric small molecule inhibitor of KSP, alters the binding mode of KSP and microtubules by blocking ADP release without affecting the dissociation of the KSP-ADP complex within microtubules, thereby inhibiting KSP mobility [42]. Ispinesib displays e cacy against diverse cancer cell proliferation and induces apoptosis, whilst also inducing tumor regression in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
“…Ispinesib, a novel, potent, selective, and allosteric small molecule inhibitor of KSP, alters the binding mode of KSP and microtubules by blocking ADP release without affecting the dissociation of the KSP-ADP complex within microtubules, thereby inhibiting KSP mobility [42]. Ispinesib displays e cacy against diverse cancer cell proliferation and induces apoptosis, whilst also inducing tumor regression in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the development of bioinformatics and genomics, the study of immune mechanisms can provide predictive value for the risk prognosis of diseases with potential benefits for patients. [7] In recent years, multiple studies have confirmed that long noncoding RNAs (lncRNAs) exhibit dynamic changes in various cardiovascular diseases and participate in disease regulation through multiple molecular mechanisms, these changes may be important for the development and progression of MI. [8] LncRNAs are defined as RNA transcripts longer than 200 base pairs and that are the main class of noncoding RNA.…”
Section: Supplemental Digital Content Is Available For This Articlementioning
confidence: 99%
“…In addition, with the development of bioinformatics and genomics, the study of immune mechanisms can provide predictive value for the risk prognosis of diseases with potential benefits for patients. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%